Pengaruh Motivasi Ekonomi, Motivasi Karir dan Biaya Pendidikan Terhadap Minat Mahasiswa Akuntansi Mengikuti Pendidikan Profesi Akuntansi - Maria Ednawati Woga; Pipiet Niken Aurelia; Yoseph Darius Purnama Rangga (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
The purpose of this research is to determine the influence of economic motivation, career motivation and educational costs on accounting students' interest in taking professional accounting education. This research uses an associative approach with a causal relationship and uses a quantitative approach. The sample was determined randomly by dividing the population into several subclasses with a sample size of 84 people. The results of this research indicate that economic motivation has no effect on accounting students' interest in pursuing professional accounting education. Career motivation influences accounting students' interest in participating in professional accounting education. Education costs do not influence accounting students' interest in participating in accounting professional education. It can be concluded that simultaneously Economic Motivation, Career Motivation and Education Costs have a significant effect on Accounting Students' Interest in Taking Accounting Professional Education